Magic of Mexico – Pueblos Mágicos in the Tourist Space of the Country - Winiarczyk-Raźniak, Anna; Raźniak, Piotr (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2019)
The tourist attractiveness of Mexico is based on its unusual nature, history and cultural richness, which can be seen at almost every step. This affects the unusual specificity of rural areas, which in many cases still function based on the traditional way of life. In turn, in the cities, the process of permeating of the pre-Hispanic and Spanish (colonial) culture is clearly visible. On top of that, the process of modernisation is additionally imposed in the largest cities, also in the cultural and physiognomic layers. Despite this, throughout the country you can still find towns that have preserved the specificity and morphology of their founding. Since 2001, SECTUR (Secretaría de Turismo) administers seven regional programs whose task is to activate local communities (located mainly in the interior of the country) through, among others, conducting a common marketing policy on tourism, as well as through the creation of joint development plans. One of them - special in terms of space - is the Pueblos Mágicos Program. As the only one, it covers the entire country and establishes cooperation between the authorities at various levels of state administration and government agencies. The aim of the article is to present the Pueblos Mágicos Program, as well as to present its strengths and weaknesses, along with the proposal to continue its operation.